Photoimmunotherapy of hepatocellular carcinoma-targeting Glypican-3 combined with nanosized albumin-bound paclitaxel. (April 2015) - Hanaoka, Hirofumi; Nakajima, Takahito; Sato, Kazuhide; Watanabe, Rira; Phung, Yen; Gao, Wei; Harada, Toshiko; Kim, Insook; Paik, Chang H; Choyke, Peter L; Ho, Mitchell; Kobayashi, Hisataka
Aim: Effectiveness of Glypican-3 (GPC3)-targeted photoimmunotherapy (PIT) combined with the nanoparticle albumin-bound paclitaxel (nab-paclitaxel) for hepatocellular carcinoma was evaluated.Materials & methods: GPC3 expressing A431/G1 cells were incubated with a phthalocyanine-derivative, IRDye700DX (IR700), conjugated to an anti-GPC3 antibody, IR700-YP7 and exposed to near-infrared light. Therapeutic experiments combining GPC3-targeted PIT with nab-paclitaxel were performed in A431/G1 tumor-bearing mice.Results: IR700-YP7 bound to A431/G1 cells and induced rapid target-specific necrotic cell death by near-infrared light exposure in vitro . IR700-YP7 accumulated in A431/G1 tumors. Tumor growth was inhibited by PIT compared with nontreated control. Additionally, PIT dramatically increased nab-paclitaxel delivery and enhanced the therapeutic effect.Conclusion: PIT targeting GPC3 combined with nab-paclitaxel is a promising method for treating hepatocellular carcinoma.